EXCRETION RATE and FEEDING ROOM VE Aeneolamia reducta (LALLEMAND) (HOMOPTERA: CERCOPIDAE) IN SIX GRASS SPECIES - CORDOBA, FREDDY; LAPOINTE, STEPHEN L.; SERRANO, MIGUEL S. (Revista Colombiana de Entomología, 1990)
The effect of six different kinds of grass on the excretion rate of the cercopid Aeneolamia reducta was studied in a screen house and a growth chamber. The main objective was to measure the excretion rate of adult A. reducta on B. decumbes c.v.Basilisk (susceptible), B. dictyoneura cv. Llanero (tolerant), B. jubata CIAT 16531 (antibiotic), and B. brizantha cv. Marandú (antibiotic). Wax membrane sachets were used for collecting insect excreta. Female A. reducta produced significantly greater quantities of excreta when placed on cv. Basilisk (1.6 ml/ insect/day) and cv. Llanero (1.5 ml/ insect/day) and cv. Marandú (0.6 ml/ insect/day). Gas chromatography of lyophilized samples of excreta of insects showed low sugar content indicating that adults fed from the xylem